HUBUNGAN SISTEM KEPERCAYAAN DAN JENIS PEKERJAAN DENGAN TINGKAT PARTISIPASI NELAYAN DALAM UPACARA ADAT SEDEKAH LAUT DI DESA GEMPOLSEWU, KECAMATAN ROWOSARI, KABUPATEN KENDAL, JAWA TENGAH - nur endah putri, febria; Sya, Ahman; Setiawan, Cahyadi (Universitas Nusa Cendana, 2024)
Sea almsgiving is a tradition that is still consistently carried out in various coastal areas of Indonesia. As a relic from ancestors that has been passed down from generation to generation, it makes people believe in myths related to the phenomenon of sea alms. Sea almsgiving itself is carried out as a form of community gratitude for the abundant marine products as well as gratitude for the safety and blessings that have been given by God Almighty in carrying out activities as fishermen. The first aim of this research is to determine the level of trust of the fishing community towards sea alms ceremonies, the second is to determine the income level of fishermen in Gempolsewu Village and the third is to determine the relationship between belief systems and type of work on fishermen's participation in traditional sea alms ceremonies. in Gempolsewu village, Rowosari District, Kendal Regency, Central Java. This research uses quantitative research methods, in determining the population the researcher uses sampling techniques and uses survey techniques for data collection. The results of this research state that the fishing community's level of trust in the sea alms ceremony is in the high category, while the fishing community's income level is in the medium category. The relationship between belief system and type of work does not show a significant relationship with fishermen's participation in the traditional sea alms ceremony in Gempolsewu village, Rowosari District, Kendal Regency, Central Java.